Where are we when the community looks for us? A social network analysis of the self-organized network #TwitterFoodBank - Hoang, Thanh Thi (Communication and the Public, 2023)
Traditional crisis management approaches have often overlooked the role of community and nonprofit organizations. In this study, we investigated how nonprofits and communities contributed to problem-solving during crises through self-organization on social media. We applied social network analysis to 17,732 interactions using #TwitterFoodBank, a self-organized network emerged during the early stage of COVID-19 to address food insecurity. Our results highlighted the significant role of nonprofits in coordinating the community’s self-organized network. However, they also revealed a lack of coordination among these organizations in maintaining a viable network. These findings have valuable implications for nonprofits seeking to leverage the potential of online self-organized communities in crisis management.
Keywords: dept.psc; peer-reviewed

Small Power: How Local Parties Shape Elections by David Doherty, Conor M Dowling and Michael G Miller - Wharton, Jonathan L. (Political Science Quarterly, 2023)
Num Pages: 3
Keywords: book.review; dept.psc

Staying Connected While Staying Distant: Social Media Engagement of Food Banks in Texas in the Wake of the COVID-19 Pandemic - Hoang, Thanh Thi (Human Service Organizations: Management, Leadership & Governance, 2023)
This study explores the social media engagement of human service nonprofits during the early phase of the COVID-19 pandemic. We analyzed 2,726 tweets from 15 food banks in Texas to understand their communication and audience engagement on social media. During the early outbreak, food banks were more active on social media, and these organizations primarily shared community-building and informational content. Before the pandemic, community-building content led to the highest engagement level. However, action and informational content saw greater engagement during the crisis. Our findings reveal that online audiences perceive the importance of each content type differently in varying circumstances. By understanding preferences and needs of online audiences, human service nonprofits can harness the power of social media to amplify their impact while operating during times of crisis.
0 citations (Crossref) [2023-10-31] _eprint: https://doi.org/10.1080/23303131.2023.2237090
Keywords: Audience engagement; crisis; dept.psc; food banks; peer-reviewed; social media

“Enquiring Minds Want to Know”: President Bill Clinton and the Blurring of News and Gossip - Hopper, Jennifer (A Gossip Politic: Rhetoric, Politics and Society, 2023)
This chapter explores the case of President Bill Clinton and the Lewinsky scandal as a pivotal moment in the convergence of political, technological, and cultural changes that elevated the presence of gossip and rumor in mainstream news sources, with major, lasting consequences. Throughout the unfolding of the scandal, unconfirmed and often salacious information about what had happened was transmitted among individuals and amplified through the media. The chapter takes a close look at some key elements contributing to such trends, including use of anonymous sourcing, heightened competition between media outlets, and the emergence of new media actors covering American politics and the presidency. An analysis of two specific incidents, involving coverage of allegations there were eyewitnesses to the president’s affair with Monica Lewinsky and that Lewinsky had a dress stained with the president’s DNA in her possession, demonstrates how prominent national news outlets publicized information reflecting weaker reporting standards and conveyed unsubstantiated rumors as news. As the news media devalued itself in cases such as this one, abandoning professional conventions and prioritizing sensational, entertaining content, the public began to no longer trust or rely on such sources to help it interpret events. We continue to see the ramifications of those developments in the present, with widespread belief in fake news, little consensus on what constitute facts or reality, and stark partisan divides about who can be relied upon to transmit the truth of political events. © 2023, The Author(s), under exclusive license to Springer Nature Switzerland AG.
Keywords: New media; President Bill Clinton; Scandal politics; The Lewinsky Scandal; dept.psc